Inquiry Learning Model with the Assistance of Paragraph Card Envelope Media to Improve the Ability to Find the Main Idea of a Text in Indonesian Language Learning - Novi Safira; Syahidan Nurdin (MANDAILING GLOBAL EDUKASIA, 2025)
This research is motivated by the low ability of students in finding the main idea of ​​a paragraph, especially in determining the main idea based on its location. Students still have difficulty distinguishing main ideas and supporting ideas in reading. This study aims to improve students' ability in finding the main idea of ​​a paragraph through the application of the inquiry learning model with paragraph card envelope media, as well as to determine the improvement in students' reading comprehension skills after the application of the model. The research method used is Classroom Action Research (CAR) which is carried out in two cycles, with stages of planning, implementation, observation, and reflection in each cycle. The subjects of the study were 18 fourth-grade students of SD Negeri 61 Banda Aceh in the 2025/2026 academic year. Data collection instruments included teacher activity observation sheets, student activity observation sheets, and reading comprehension tests. The results showed that teacher activity increased from 67.5% in cycle I (good category) to 88.75% in cycle II (very good category). Student activity also increased from 65.6% in cycle I (sufficient category) to 85.93% in cycle II (very good category). In addition, students' ability to find the main idea increased significantly, from 44.4% in cycle I (sufficient category) to 83.3% in cycle II (very good category). Based on these results, it can be concluded that the application of the inquiry learning model with paragraph card envelope media is effective in improving the ability of fourth grade students of SD Negeri 61 Banda Aceh in finding the main idea of ​​a paragraph, both based on its location and in distinguishing the main idea and supporting ideas.